Evaluation of morphological characteristic and varieties of tongue prints for personal identification in Kanpur communities: An impression-based analysis - Kriti Garg; Rohan Sachdev; Samiksha Shwetam; Shubhra Saxena; Vishal Mehrotra; Akash Srivastava (Wolters Kluwer Medknow Publications, 2020)
Context: The human tongue, a unique organ with complex architecture, exhibits significant morphological variations in the human body consistent with its complex role. Its morphological characteristic features and varieties can go about as proof of life and can be used for personal identification. The morphology and surface highlights of the tongue are qualities of each person, and these characteristics can be utilized as legal distinguishing proof of each person. Aims: This study is aimed to analyze varieties in morphological qualities of the tongue and to find out gender differences. Settings and Design: This study was conducted on 206 (Group I consist of 105 females and Group II consist of 101 male) participants with an age range of 21-30 years for 4 months who had visited the Department of Oral Medicine and Radiology. Subjects and Methods: The tongue was exposed to visual assessment following which alginate impression of the dorsal surface of the tongue was taken to make tongue cast and to assess distinct morphological features of the tongue and its variations in males and females. Statistical Analysis Used: The discrete (categorical) data were summarized in number (n) and percentage (%) and compared using the Chi-square (χ2) test. Results: A total of 206 participants in both groups, the U-shaped tongue, was the most common findings in males, as well as in females followed by a V-shaped tongue with a sharp tip that was observed more in females compared to males. Scalloped borders and multiple fissures were more common in males as compared to females. Conclusions: Variations of tongue shape and surface properties can be used as personal human identification in forensic odontology, and tongue prints can also be used as a standard method for the collection of data. The collected data of tongue prints may be used as a professional recognition database to ease human identification and to avoid future scams.